Work Values dan Situational Awareness Pada Guru Pendamping Khusus (GPK) di Banjarmasin - Marleni, Siti Mutiara; Ceria Hermina; Dicky Listin Quarta (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2024)
Children with special needs have the same rights to receive the best learning experiences to develop their potential optimally, one of which is through the presence of Special Assistant Teachers (SAT). However, the number of SATs in Indonesia is still insufficient compared to the number of children with special needs, which can hinder their progress. Situational awareness of SATs becomes an important factor in effectively assisting children with special needs. This study aims to determine whether there is a relationship between situational awareness and work values in SATs. This research uses a quantitative approach with a correlational design. The data collection tools used are situational awareness and work values scales. Purposive sampling technique with a total of 116 SATs was used in this study. The data analysis used is Spearman rank correlation. The results of the study show a positive relationship between situational awareness and work values, which means that the higher the work values, the higher the situational awareness of SATs in Banjarmasin.